MONITORING SYSTEM OF PLAGIARISM IN STUDENT WORKS - Шинкаренко, Віктор Іванович; Куроп’ятник, Олена Сергіївна (Eastern-European Journal of Enterprise Technologies, 2012)
In the article a brief description of software for detecting a plagiarism in texts is given. Approach on graphs for modeling and text analysis for the presence of plagiarism is proposed. The preliminary results of development of control system is presented, which base on the mentioned approach.